Análise funcional da constituição - Pessoa, Roberto Hugo Lima (2008)
Constitutional law scholars often refer, in their jurisprudential writings, to the function (or functions) of the constitution. It is not always clear, however, what they actually mean with such language. This dissertation aims to contribute to the understanding of the functional analysis of the constitution, enabling the proper development and the critical analysis of legal jurisprudence on the <<functions of the constitution>>. For such purpose, based on specialized bibliography in the Science of Law, as well as in the Philosophy of Science and other Social Sciences, three possible <<comprehension models>> of the functional studies of the constitution are developed (constitution as artifact, constitution as integration mechanism, and constitution as garden of Justice), and their main scientific implications and challenges are indicated